ANALISIS FOTO JURNALISTIK PADA KANTOR BERITA AGENCE FRANCE PRESSE (AFP) TENTANG PENERAPAN SYARIAT ISLAM DI ACEH TAHUN 2017 - Fakhri Fakhri; Heri Juanda (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2020)
The public spotlight through mass media coverage of Islamic law is still happening. Agency France Presse (AFP) is one of the global news agencies whose role is to supply photos to various media around the world, including photos about the implementation of Islamic law in Aceh. In its reporting, AFP tends to perceive the application of Islamic Sharia in Aceh as violating human rights and intolerance of other religions. This research aims to find out how the AFP news agency reports about the implementation of Islamic law in Aceh through the photos they broadcast. This study used a qualitative descriptive method using the Robert N Entman framing analysis theory. The results showed that the content of the photo broadcast by AFP on Islamic law in Aceh defines the problem of caning as one of the implementation of Islamic law as a form of violence that is contrary to the ideology of the international community so that its reporting tends to cause controversy. Likewise in writing its photo captions, AFP emphasizes certain issues by providing repetitions of a problem so that photos related to the application of Islamic law become high news value and are able to attract subscribed overseas media. AFP tends to describe violence and things that give the impression that the application of Islamic law in Aceh violates human rights (HAM).Keywords: Photo Journalism, Islamic Sharia, Mass Media